Pengaruh Brand Image dan Brand Trust terhadap Brand Loyalty Astra Honda Motor pada Nirmala Motor Samarinda - Anisa Nurulita; Gusti Noorlitaria; Asnawati Asnawati (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
This study aims to identify and analyze the effect of Brand Image and Brand Trust jointly (simultaneously) to Brand Loyalty Astra Honda Motor and identify and analyze the variables that affect the dominant Brand Loyalty Astra Honda Motor By NIRMALA MOTOR Samarinda, using linear regression analysis regression. The results showed regression coefficient has a positive sign, which means that if the values of two variables Brand Image and Brand Trust increases or increases, it will be able to improve on Brand Loyalty Astra Honda Motor By NIRMALA MOTOR Samarinda. this is evidenced by the R value of 0.622 means that there is a strong relationship of variable Brand Image and Brand Trust on the Brand Loyalty. The coefficient of determination (R2) of 0.386 or 38.60%, this shows the proportion of variable contribution Brand Image and Brand Trust to fluctuations Brand Loyalty. The rest was influenced by variables outside the research. Simultaneously prove that the variable Brand Image and Brand Trust effect on Brand Loyalty. This is evidenced from the calculation of the F test (simultaneous) obtained value of F Ftable. This means that the variable Brand Image and Brand Trust jointly (simultaneously) influence on Brand Loyalty Astra Honda Motor By NIRMALA MOTOR Samarinda. Thus the first hypothesis is proven correct or acceptable. The results of the partial test of the two variables Brand Image and Brand Trust on the Brand Loyalty the dominant influence is variable Brand Image this is evidenced by the value of the standardized coefficients (beta) Brand Image variable that is larger than the standardized coefficients (Beta) for variable Brand Trust. Thus the second hypothesis in this study proved to be true or acceptableKeywords: Brand Image and Brand Trust and Brand Loyalt